IMMUNOHISTOCHEMICAL EVALUATION OF OESTROGEN RECEPTORS IN ADENOID CYSTIC CARCINOMA OF SALIVARY GLAND - Mujtaba, Hasan; Atique, Muhammad; Batool, Iffat; Umer, Muhammad Farooq (Journal of Ayub Medical College Abbottabad, 2017)
Background: Oestrogen has a physiological role throughout the body including oral cavity. The effects are mediated by binding to two receptors in nucleus alpha and beta, which are ligand-activated transcription factors. The alpha receptors have a prognostic significance in cancer of breast while in Adenoid cystic carcinoma of salivary glands the results are inconsistent. This study was conducted to determine the oestrogen receptor Alpha staining in adenoid cystic carcinoma of salivary gland. Methods: Paraffin blocks of thirty cases of adenoid cystic carcinoma of salivary gland were retrieved and evaluated through immunohistochemistry by anti-oestrogen antibody clone 1D5.The intensity and proportion of nuclear staining was scored using Allred scoring system. Results: From total of thirty cases, 5 cases expressed as mild staining of oestrogen receptors using Allred scoring system. Three cases of cribriform and two cases from tubular pattern expressed positivity. In the case series selection of our study cohort there was no association seen in age, gender, site and histological type of tumour with the expression of oestrogen receptor. Conclusion: Role of oestrogen is well established in breast cancers, some of salivary gland adenoid cystic carcinoma also express these receptors and could be involved in the pathogenesis. Further studies are recommended to seek possible explanation of variable staining pattern observed in many other studies, and also to determine the possible therapeutic use of tamoxifen in such tumours. Keywords: Adenoid cystic carcinoma of Salivary Gland; Oestrogen receptor; Immunohistochemistry